Effect of Replacement of Tubifex sp. with Artificial Feed on Growth And Survival Rate of Common Snakehead Larvae (Channa striata) - Sadewi Septim Utami; Netti Aryani; Nur Asiah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract The purpose of this study was to determine the effect of the replacement of Tubifex sp. with artificial feed on the growth and survival rate of common snakehead larvae (channa striata). This research was conducted in Februari – April 2020 at the Fish Hatchery and Breeding Laboratory, Fisheries and Marine Science Faculty, Riau University. The method used was an experimental method using a one-factor Completely Randomized Design (CRD) with five treatments and three replications. The treatments of this study were T40PB0 (Tubifex sp. 40 days + Artificial Feed 0 day), T0PB40 (Tubifex sp. 0 day + Artificial Feed 40 days), T30PB10 (Tubifex sp. 30 days + Artificial Feed 10 days), T20PB20 (Tubifex sp. 20 days + Artificial Feed 20 days), T10PB30 (Tubifex sp. 10 days + Artificial Feed 30 days). The larvae used were five days old. Larvae are kept in an aquarium of 15 liters of water with a stocking density of 2 fish/liter for 40 days. 80% of the weight of biomass for Tubifex sp. and 13% of the weight of biomass for artificial feed. The result showed that the best treatment was T30PB10 (Tubifex sp. 30 days + Artificial Feed 10 days) was the highest growth (1,73 g, 3,84 mm, and 16,10%/day), the best feed efficiency was 44,78%, and the highest survival rate was 88,89%.Keywords: Common snakehead larvae, Tubifex sp., Artificial Food, Survival Rate